Delayed Addition Foaming of Bio-epoxy Blends: Balancing Performance Requirements and Sustainability - Shukla S.; Agnihotri S.; Pradeep S.A.; Pilla S. (My University, 2025)
In this work two material systems, epoxidized pine oil (EPO) and acrylated epoxidized soybean oil (AESO), both previously individually experimented on, were blended in varying ratios, foamed, and characterized with respect to their microstructure, physical properties, mechanical performance, and thermal stability. Intermediate systems were created bearing a broad range of properties derived from both the parent material systems. The structure-property relations were studied, and the effect of process parameters on the resulting thermomechanical behavior was analyzed. Finally, the degradation kinetics of the developed foams was studied, and activation energies were calculated for a comprehensive understanding of behavior of foams at high temperatures. The obtained foams exhibited high thermal stability and mechanical strength varying from 0.4 to 11.3 MPa for densities ranging from 0.76 to 0.50 g/cm3, respectively, which enables them to be employed in a variety of applications based on product requirements. © 2018 American Chemical Society.